Encapsulation of Crabtree's catalyst in sulfonated MIL-101(Cr): enhancement of stability and selectivity between competing reaction pathways by the MOF chemical microenvironment - Rosseinsky, M; Grigoropoulos, A; McKay, A; Katsoulidis, A; Davies, R; Haynes, A; Brammer, L; Xiao, J; Weller, A (Wiley, 2018)
Crabtree's catalyst was encapsulated inside the pores of the sulfonated MIL-101(Cr) metal-organic framework by cation exchange. This hybrid catalyst is active for the heterogeneous hydrogenation of non-functionalized alkenes either in solution or in the gas phase. Moreover, encapsulation inside a well-defined hydrophilic microenvironment enhances catalyst stability and selectivity to hydrogenation over isomerization for substrates bearing ligating functionalities. Accordingly, the encapsulated catalyst significantly outperforms its homogeneous counterpart in the hydrogenation of olefinic alcohols in terms of overall conversion and selectivity with the chemical microenvironment of the MOF host favouring one out of two competing reaction pathways.